Standalone Axial Malrotation after Pediatric Supracondylar Fracture Does Not Seem to Be an Indication for Immediate Postoperative Revision Surgery - Frederik Greve; Michael Müller; Markus Wurm; Peter Biberthaler; Georg Singer; Holger Till; Helmut Wegmann (MDPI AG, 2022)
Rotational spurs as evidence for post-surgical malrotation are frequently observed when treating pediatric supracondylar humeral fractures (SCHFs). This study aimed to investigate the long-term outcome of a pediatric cohort with unrevised axial malrotation and to discuss the indication for revision surgery. Postoperative radiographs of children treated for SCHFs over eight years were retrospectively analyzed. Children with radiological signs of malrotation (von Laer malrotation quotient) were invited for a follow-up clinical and radiological examination. Among 338 treated children, 39 (11.5%) with a mean age of 5.3 years (range 1.8-11.7 years) showed radiological signs for postoperative malrotation and were not revised and therefore invited to participate in the study. Twelve patients (31%) with a mean age of 11.3 years (range 8.8-13.8 years) took part in the follow-up examination after a mean of 7.1 years (range 5.4 to 11.3 years). The mean postoperative van Laer malrotation quotient was 0.15 (range 0.11-0.2). At follow-up, the range of motion of the elbow joint was not significantly different compared to the contralateral side. Apart from the humeral ulnar angle (p = 0.023), there were no significant differences in the radiological axes. The Flynn criteria were excellent and good in 90% of the cases. The mean was 1.7 points indicating excellent subjective results. Standalone postoperative malrotation did not lead to an adverse long-term outcome in a small cohort of pediatric patients with SCHFs and did not indicate immediate postoperative revision surgery. However, further investigations with larger cohorts should verify whether additional criteria such as stability of the osteosynthesis and signs for increasing valgus or varus displacement in the follow-up radiographs should get more importance in decision making.